BACHA POSH : KEJAHATAN KEMANUSIAAN DI DALAM SELIMUT TRADISI DAN KEBUDAYAAN NEGARA AFGHANISTAN - Arinta Fridha Pangestika (Journal of International Relations Diponegoro, 2022)
ABSTRACT             Sexual harassment, beatings and trafficking of women and children are things that are often faced by women in Afghanistan. Although the Bacha Posh Tradition is not in accordance with the fulfillment of individual rights for women and girls in Afghanistan, this Tradition has later developed into a culture that is inherent in society as the only way for women to gain their freedom and rights regarding education and work. In accordance with the Theory of Cultural Relativity used by researchers in this study, however, the impact that occurs due to the ongoing Bacha Posh Tradition is ultimately ruled out because of the feelings that are inherent in every girl in Afghanistan. The Bacha Posh tradition becomes a responsibility and obligation that girls have to do to help the family's economy and provide much easier access to resources for their families. Afghanistan Independent Human Rights Commission or AIHRC as an independent human rights enforcement agency in Afghanistan also regrets the attitude and actions taken by the Afghan government with the lack of analysis related to the risks of violations that arise such as violations of Human Rights through the Bacha Posh Tradition. Unfortunately, the return of the Taliban to Afghanistan will bring misery and a much worse life for the Afghan people in the future. Therefore, the researcher tries to explain the impact of what happened to women and girls in Afghanistan related to the implementation of the Bacha Posh Tradition in response to violations that arose in Afghanistan after the Taliban occupation. Researchers also try to provide conclusions related to this. In the end, this tradition becomes a unity in society and merges as a culture that is closely related to the views of Islamic law. The implementation of the Bacha Posh Tradition which is based on a sense of responsibility and its implementation which is used as a form of community jihad in terms of their belief in Islamic law is very clear, making this tradition difficult to separate from Afghan society.